Synthesis and discovery of mixed-anion nitride materials - Storck, Emily N., author; Neilson, James R., advisor; Ackerson, Chris J., committee member; Ma, Kaka, committee member (Colorado State University. Libraries, 2023)
The ability to synthesize heteroanionic (or mixed-anion) materials is an important area in solid-state chemistry research. Mixed-anion compounds offer the potential to provide more desirable functionality compared to single-anion systems. However, mixed-anion systems are underexplored compared to single-anions. This is especially true for nitride materials when compared to oxides, because nitrides are difficult to make. The ease of making most oxides is due to the reactivity of oxygen and the thermodynamic stability of metal oxides, whereas the strong triple bond of N2 leads to its low reactivity and therefore difficulty in making nitrides and oxynitrides. Therefore, improved synthetic routes to produce these mixed-anion compounds are needed to unlock the potential of this underexplored phase space. This thesis describes the use of solid-state metathesis reactions to produce heteroanionic ZrNCl through reaction between AyNCl (A = Zn, Mg, or Li) precursors and ZrCl4. This thesis also highlights the use of flux reactions in attempts to synthesize new oxynitride materials based on the hypothesis that alkali halide salts have the ability to solublize nitrogen and raise its chemical potential relative to the chemical potential of nitrogen in traditional solid-state reactions to produce nitrides and oxynitrides, allowing for incorporation into products to form an oxynitride material. Here, a eutectic flux mix, LiCl-KCl, was used in the reaction between V2O3 and Li3N to synthesize vanadium containing compounds along with preliminary experiments to ascertain their stiochiometry.